2015
DOI: 10.1002/ajmg.a.37375
|View full text |Cite
|
Sign up to set email alerts
|

A PIGN mutation responsible for multiple congenital anomalies–hypotonia–seizures syndrome 1 (MCAHS1) in an Israeli–Arab family

Abstract: Mutations in the PIGN gene involved in the glycosylphoshatidylinositol (GPI) anchor biosynthesis pathway cause Multiple Congenital Anomalies–Hypotonia–Seizures syndrome 1 (MCAHS1). The syndrome manifests developmental delay, hypotonia, and epilepsy, combined with multiple congenital anomalies. We report on the identification of a homozygous novel c.755A>T (p.D252V) deleterious mutation in a patient with Israeli–Arab origin with MCAHS1. The mutated PIGN caused a significant decrease of the overall GPI-anchored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 16 publications
2
27
1
Order By: Relevance
“…The patients in this study showed features mostly matched to those of MCAHS2 (van der Crabben et al., ; Johnston et al., ; Kato et al., ; Tarailo‐Graovac et al., ), and may be classified into a less severe type of PIGA deficiency, which did not show severe congenital anomalies (Tarailo‐Graovac et al., ). The phenotypes of our patients also showed certain similarity to MCAHS1 and MCAHS3 (Khayat et al., ; Nakagawa et al., ; Ohba et al., ). However, no pathogenic variants of PIGN or PIGT genes have been found in our patients.…”
Section: Discussionsupporting
confidence: 73%
“…The patients in this study showed features mostly matched to those of MCAHS2 (van der Crabben et al., ; Johnston et al., ; Kato et al., ; Tarailo‐Graovac et al., ), and may be classified into a less severe type of PIGA deficiency, which did not show severe congenital anomalies (Tarailo‐Graovac et al., ). The phenotypes of our patients also showed certain similarity to MCAHS1 and MCAHS3 (Khayat et al., ; Nakagawa et al., ; Ohba et al., ). However, no pathogenic variants of PIGN or PIGT genes have been found in our patients.…”
Section: Discussionsupporting
confidence: 73%
“…The existence of PIGN -associated deficiency diseases indicates that this ethanolamine phosphate side chain has an important biological function, probably related to its role in the recognition of GPI glycolipids by the transamidase complex that attaches proteins to the GPI anchors [48]. Flow cytometry has been used to demonstrate altered expression of these proteins with mutations of PIGN in humans [38, 4951].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Individuals born with other homozygous or compound heterozygous PIGN mutations share a developmental deficiency syndrome known as multiple congenital anomalies-hypotonia-seizures syndrome-1 or MCAHS1 (OMIM #614,080). The current literature describes at least 17 MCAHS1 patients from 9 families carrying 13 different PIGN mutations [38, 4951, 54, 55]. These patients had neonatal hypotonia, severe developmental delays, congenital anomalies, visual impairment, hyporeflexia, tremors, and seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in addition to the original mutation (Maydan et al, 2011), many new recessive PIGN mutations, mostly missense mutations, have been reported in patients with MCAHS1 (Brady et al, 2014;Couser et al, 2015;Fleming et al, 2015;Khayat et al, 2015;Nakagawa et al, 2015;Ohba et al, 2014). In addition to MCAHS1, PIGN mutations with premature stop codons have been identified in patients suffering from Fryns syndrome, a condition that shares some symptoms, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Autosomal-recessive mutations in the human PIGN gene were identified in patients with multiple congenital anomalies-hypotoniaseizures syndrome 1 (MCAHS1, Online Mendelian Inheritance in Man, OMIM 614080) (Maydan et al, 2011). In addition to the original mutations reported in patients with this disease, many recessive missense PIGN mutations have also been identified in patients with MCAHS1 (Brady et al, 2014;Couser et al, 2015;Fleming et al, 2015;Khayat et al, 2015;Nakagawa et al, 2015;Ohba et al, 2014). Recently, some patients with Fryns syndrome (OMIM 229850), which causes lethality during the neonatal period through congenital diaphragmatic hernia (CDH) and other associated malformed features, have also been reported to harbor recessive mutations in the PIGN gene (McInerney-Leo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%